Something borrowed [compact disc, unabridged] - Giffin, Emily (BBC Audiobooks America, 2009)
After a night of indiscriminate partying, Rachel sleeps with a close friend's fiancé and is consumed with guilt, until the intensity of her feelings forces her to make a difficult choice.